Effect Of Different Biodiesel Blends On Engine Performance, Emissions And Combustion Characteristics Under Various Engine Torques And Speeds Condition - Chow, Hong Man (Universiti Sains Malaysia, 2022)
The experimental background is to determine a solution for combating the energy shortage issue using renewable fossil fuel to alternative energy sources in diesel engine. Biofuels is the choice of renewable fuels since the past decade as renewable and biodegradable fuels. Globally, the urge and support of government to promote the usage of biofuels mixing with diesel blend for the betterment of environment without jeopardizing the engine performance. Most of the researchers believe fossil fuels is a source of clean energy when mixed with biofuel, and they have conducted research of utilizing biofuels in diesel engine. The experiment is conducted by utilizing biodiesel-diesel blend (B0, B20, B40, B60, B80 and B100), at various engine load such as 25%, 50%, 75% and 100% and engine speed of idle, 2350rpm, 3100rpm and 3850rpm to test the performance and emissions of a diesel engine. The performance results are the Power, Brake Thermal Efficiency (BTE), Brake Specific Fuel Consumption (BSFC), and emissions such as Nitrogen Oxide (NOx) and Soot. For all the tested biodiesel data is obtained by using the Labview and DeweSoft software, simulation is conducted by using the RK Diesel software to verify the data accuracy, and the choosing of best biodiesel mixing ratio, engine speed and engine load, to find the maximum BTE and BSFC with the minimum achievable emissions of NOx and soot is conducted by accessing the Design-Expert software. The results of the experiments indicate that biodiesel B60, speed of 2070rpm, Load of 55% is the optimum choice to maximize the BSFC, BTE and engine power, with the minimization of the engine emissions performance.